UNDERSTANDING OF SMES IN THE PREPARATION OF MSME BOOKKEEPING BASED ON FINANCIAL ACCOUNTING STANDARDS FOR MICRO, SMALL AND MEDIUM ENTITIES (SAK EMKM) IN THE COMMUNITY OF PAHLAWAN VILLAGE, BATUBARA REGENCY, NORTH SUMATRA - Neng Sri Wardhani; Annisa Ilmi Faried (Proceeding International Seminar of Islamic Studies, 2023)
MSME initiatives help create jobs and are very important in helping Batubara District in solving its financial problems to boost the local economy and improve the welfare of its residents, especially in Pahlawan village, Tanjung Tiram District. The purpose of this study is to determine how well the understanding and readiness of MSME actors and the Pahlawan village community in Batubara Regency to implement MSME bookkeeping based on Micro, Small and Medium Entity Accounting Standards (SAK EMKM) in 2023, which is beneficial for MSME business continuity for MSME actors. Primary and secondary data are used to collect data. Primary data was obtained from the distribution of questionnaires and secondary data was obtained from data from the Cooperative and MSME Office of Coal Regency. This study used a sample of 30 people from Pahlawan village, Batubara Regency, including MSME actors. Because this study discusses the understanding of MSME bookkeeping based on the Financial Accounting Standards of Micro, Small and Medium Entities (SAK EMKM) in Coal Regency, Therefore, descriptive qualitative research methodology in the form of words instead of numbers is used to present the data in this study.